O-EG002. 8-Year experience of stereoelectroencephalography at Westmead Hospital and the Children's Hospital at Westmead. Issue 8 (August 2021) - John Phamnguyen, Thienan; Dexter, Mark; Bleasel, Andrew; Gill, Deepak; Gupta, Sachin; Wijayath, Manori; Rahman, Zebunnessa; Bartley, Melissa; Wong, Chong
Abstract : Introduction . We report our surgical series of intractable epilepsies investigated with stereoelectroencephalography (SEEG) at Westmead Hospital and The Children's Hospital at Westmead; evaluating the methodology, complication rate and seizure outcome from an 8-year program. Methods . 82 SEEG were performed in 80 patients (males, n = 45) at Westmead Hospital and The Children's Hospital at Westmead from 2012 to 2019. All SEEG were performed using frame-based stereotaxy with CRW (Integra, Plainsboro, NJ, USA) frame systems. Clinical demographics, methodology, outcomes and complications were collected and analysed. Results . Mean age of patients was 22 years old (range 4–49 years old). Two patients had two SEEG implantations because the initial implantation did not provide sufficient information to inform resection. Fifty-six patients had normal MRI. A total of 1132 electrodes were inserted in 82 SEEG procedures (mean number of electrodes per SEEG = 14, range 8–21; total number of electrode contact = 14611). Majority of patients had unilateral implantation (left = 24, right = 32, bilateral = 24). Complications occurred in four patients (subdural haemorrhage = 3, fractured electrode = 1). All patients were able to proceed with VEEG monitoring after electrode implantation. Seizures were recorded in 81 SEEG studies. One patient did not have any seizures during the evaluation. 72% of patients underwent resective surgery following SEEG. Two patients were offered resective surgery but had declined. 26% of patients were not localised. 13 patients were awaiting surgery or pending conference decision. 74% became seizure free after resective surgery. Conclusion . SEEG can be a relative safe and effective methodology for defining the epileptogenic zone.